The Study of Local Atomic Structure and Phase Transition with Effecting on Piezoelectric Property of (1-x)BNT-xBCST Ceramics by Using Synchrotron and Raman Spectroscopy Technique - Kronphom, Chittakorn; Reabreang, Nathanan; Sangsoda, Passanan; Bongkarn, Theerachai; Kidkhunthod, Pinit (Burapha Science Journal, 2026)
In this research, the study of the phase formation, the local atomic structure and phase transition on piezoelectric property of (1-x)BNT-xBCST solid solutions at various of x content prepared via the solid state combustion technique, using glycine as fuel, were studied. The study results, it was found that (1-x) BNT-xBCST ceramics exhibited a single perovskite structure with the co-existence of the rhombohedral and tetragonal phases. Then, it was observed that the concentration of BCST compound with increasing of x affected the Ti atom position which led to change phase formation. From the Raman spectroscopy result, it can be see that the Raman spectrum can confirmed the co-existence of the rhombohedral and tetragonal phases at x = 0.04. When x content over 0.04, the ceramics showed higher tetragonal phase. The piezoelectric coefficient (d33) increases when x content increases up to 0.07 and then decreased. At x content of 0.07, the sample has the highest density (5.93 g / cm3) and the highest d33 (202 pC/N).